Repeatability and reproducibility of a clinical device for Brillouin microscopy to measure the biomechanics of the anterior segment of the eye: In vivo tests - Hannah Pearl Glucksman; Andrew Shin; Lawrence Yoo; Luis Alberto Carvalho; Claire Shelley Barnes (PLoS ONE, 2026)
Purpose We performed a prospective study to assess the repeatability and reproducibility of the novel Brillouin Optical Scanning System (BOSS ® ) in measuring the biomechanical properties of the cornea and crystalline lens in vivo, to determine device utility in a clinical setting. Methods Adult study participants underwent standard ophthalmic exams to confirm eligibility. At two separate visits to the clinic, monocular lens scans and corneal scans (one point and seven points, respectively) were performed three times on each of three BOSS devices, operated by different technicians. The measured Brillouin parameters per person included the lens stiffness and the stiffnesses (e.g., “Mean”, “Minimum”) across the seven corneal points. Results were combined across participants to calculate the coefficients of variation (CVs) for repeatability (within each device) and reproducibility (across devices), along with the repeatability and reproducibility limits (2.8 times the respective standard deviations). Results Eleven of the 33 participants (ages 24–72 years; 15 females) had keratoconus (5 with prior crosslinking, 3 without crosslinking, and 3 post-keratoplasty); the other 22 participants were visually normal. There were no adverse events. The average lens stiffness was 3.33 ± 0.052 GPa (mean ± SD), with an overall repeatability CV of 1.6%, with values ranging from 3.35 ± 0.037 GPa with a CV of 1.1% to 3.30 ± 0.071 with a CV of 2.1% across the separate devices. The mean corneal stiffness was 2.83 ± 0.031 GPa, with an overall repeatability CV of 1.1%, ranging from 2.85 ± 0.015 with a CV of 0.5% to 2.81 ± 0.036 with a CV of 1.3% across devices. The reproducibility CVs were 2.1% and 1.6% for lenses and corneal Means, respectively. Conclusions The study results demonstrated consistent stiffness values for both lenses and corneas within and between the three BOSS devices tested. The study shows that this device could be a useful new biomechanics-measuring tool for applications in ophthalmology.